Lumbosacral Interbody Fusion Using a Biportal Endoscopic Technique for Patients with Multilevel Severe Degenerative Lumbosacral Spondylosis: Technical Note and Case Presentations - Jung, Seok Bong; Kim, Nackhwan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Open decompression and posterior interbody fusion are standard surgical interventions for multilevel degenerative lumbosacral spondylosis (DLS). Despite their clinical efficacy, intraoperative and postoperative complications have led to the demand for a minimally invasive approach. A biportal endoscopic approach is an advanced minimally invasive surgical option.Methods The data of two patients with multilevel DLS who had undergone biportal endoscopic spine surgery (BESS) were retrospectively analyzed. Parameters such as surgical difficulty, duration of operation, blood loss, length of hospital stay, and postoperative complications were reviewed. Pain and functionality were assessed using the visual analog scale (VAS) and the Oswestry Disability Index (ODI), respectively.Results Both patients were women and aged 75 and 73 years; they complained of back pain, claudication, pain and weakness in the lower extremities, and gait disturbance. The symptoms lasted 5 and 8 years, respectively. The multilevel BESS approach was applied bilaterally. Dissection, laminofacetectomy, decompression, excision, cage insertion, and screw implantation were performed. The operation durations were 170 and 160 minutes with blood loss of 500 and 650 mL, respectively. Back pain, leg pain, and ODI scores significantly improved; no pseudoarthrosis or additional neurologic deficits were noted on follow-up.Conclusions The presented BESS technique is a minimally invasive treatment option for patients with multilevel DLS, which typically requires a complicated surgical approach. Randomized controlled studies with larger sample sizes and longer follow-up periods are needed to verify the superiority of this operation.
Keywords: lumbosacral disk degeneration disorders; endoscopic biportal surgery; minimally invasive spine surgery; lumbar interbody fusion; degenerative spondylosis